Absorbate-induced ordering and bilayer formation in propanol-graphite-oxide intercalates. (April 2016) - Cabrillo, Carlos; Barroso-Bujans, Fabienne; Fernandez-Perea, Ricardo; Fernandez-Alonso, Felix; Bowron, Daniel; Bermejo, Francisco Javier
Abstract: Real-time intercalation of liquid 1-propanol within graphite oxide prepared by Brodie's method has been monitored by means of state-of-the-art neutron diffraction. We have developed a data analysis based on the paracrystalline theory which enables the characterization of stacking disorder in terms of the average number of layers contributing to Bragg scattering and the relative dispersion of the distribution of interlayer distances. We find that monolayer intercalation expands the interlayer spacing from 5.63 Å up to 9.24 Å, a process which is accompanied by noticeable improvement of stacking order. Thermally activated mobility of the molecular adsorbate is observed down to ≈130 K, followed by the emergence of a two-dimensional glassy state below such temperature. Heating at a slow rate from this kinetically arrested state, leads to an adsorbate-driven ordering transition at ≈180 K, followed by formation of a stable structure of the propanol-graphite-oxide system. This new phase enables reversible bilayer formation and also is found to persist upon removal of excess propanol in vacuo . The final propanol-graphite-oxide composite is characterized by an interlayer distance of 8.95 Å, a much-improved ordering relative to its graphite-oxide precursor, and a pillar density of one intercalant molecule for every nine "graphene-like" carbon hexagons. Graphical abstract: